Comparing the Scandinavian automobile taxation systems and their CO2 mitigation effects. Issue 10 (28th September 2022) - Østli, Vegard; Fridstrøm, Lasse; Kristensen, Niels Buus; Lindberg, Gunnar
Abstract: Despite their similarities, Scandinavian countries have adopted starkly different automobile tax regimes. The Danish system entails very high and convex tax rates with moderate CO2 differentiation. In Norway, tax rates are high and convex with strong CO2 differentiation and total exemptions for zero emission vehicles, even from value added tax. Sweden practices feebates – CO2 dependent subsidization along with moderate taxation. Relying on a disaggregate discrete choice model of automobile purchase, we simulate the demand for passenger cars as of 2016 in Norway under a set of conditions resembling, respectively, the Danish, Norwegian or Swedish fiscal incentives before and after recent reforms. In all cases, implications are derived in terms of energy technology market shares, average type approval CO2 emission rates, and aggregate fiscal revenue. The automobile taxation system is seen to have remarkable impacts on all three accounts. In essence, among the three jurisdictions examined, the Norwegian fiscal regime has by far the strongest CO2 abatement effect. The Danish system is less effective in terms of CO2 abatement, but provides twice as much government revenue. The Swedish feebate strategy is by far the least effective in terms of both CO2 mitigation and revenue collection. Highlights: Automobile taxation is a powerful greenhouse gas abatement instrument. Tax exemptions for battery electric cars accelerate their market uptake. The disparate experiences of the three Scandinavian countries are quite instructive.